Effects of prostaglandin E1 on reperfusion injury patients: A meta-analysis of randomized controlled trials. Issue 15 (April 2017) - Zhu, Houyong; Xu, Xiaoqun; Ding, Yu; Zhou, Liang; Huang, Jinyu
Abstract: Background: Prostaglandin E1 (PGE1) is widely used as a pretreatment for myocardial reperfusion injury in animal experiments. However, the cardioprotective effects of PGE1 in patients have not been established. We performed a meta-analysis to investigate whether PGE1 is cardioprotective, based on the reduction of correlative reperfusion injury events (CRIE), major adverse cardiac events (MACE), and biomarker release in patients with ischemia reperfusion injury. Methods: The Medline, EMBASE, and Cochrane databases were searched for randomized clinical trials confirming the effects of PGE1. Two investigators independently selected suitable trials, assessed trial quality, and extracted data. Results: Six studies in patients undergoing percutaneous coronary intervention (4 studies) and cardiac surgery (2 studies), comprising a total of 445 patients, were included in this review. The results showed that PGE1 reduced the incidence of CRIE (relative ratio 0.4 [95% confidence interval 0.43, 0.95]), the incidence of MACE (0.35 [0.17, 0.70]), and the level of troponin T (standardized mean difference 20.28 [20.47, 20.09]), creatine kinase-MB (−1.74 [−3.21,  − 0.27]), interleukin-6 (−1.37 [−2.69,  − 0.04]), and interleukin-8 (−2.05 [−2.75,  − 1.34]). Conclusion: PGE1 may have beneficial effects on myocardial reperfusion injury in the clinic.